2012
DOI: 10.1002/elan.201200257
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Palladium Nanoalloys Modified Carbon Ionic Liquid Electrode with Enhanced Electrocatalytic Activity Towards Formaldehyde Oxidation

Abstract: Electrocatalysis of the oxidation of formaldehyde on silver‐palladium‐modified carbon ionic liquid electrode (AgPd/CILE) was investigated in 0.1 M NaOH. The electrochemical performance of the AgPd/CILE was compared with those of Pd/CILE and Ag/CILE. Ag plays an important role in the catalytic performance of AgPd nanocatalyst and yields an excellent antifouling effect. Amperometric measurements showed that AgPd/CILE is a promising sensor for the detection of formaldehyde in the range of 10.0 µM–70.0 mM with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…which are the energy materials for fuel cells. 19,20 Our early work shows that at platinum electrode in bis(trifluoromethylsulfonyl)imide (NTf 2 ) based ILs facile methane electro-oxidation was observed at room temperature in the presence of air, suggesting a unique catalytically active Pt–NTf 2 interface for electron transfer reaction of methane. 21 It is suggested that NTf 2 − can adsorb on the platinum metallic oxide surface 22 and coordinate with platinum to form an organic complex 23 which served as an catalyst for methane oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…which are the energy materials for fuel cells. 19,20 Our early work shows that at platinum electrode in bis(trifluoromethylsulfonyl)imide (NTf 2 ) based ILs facile methane electro-oxidation was observed at room temperature in the presence of air, suggesting a unique catalytically active Pt–NTf 2 interface for electron transfer reaction of methane. 21 It is suggested that NTf 2 − can adsorb on the platinum metallic oxide surface 22 and coordinate with platinum to form an organic complex 23 which served as an catalyst for methane oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Pd, Ag and PdAg alloys are catalytically active for a wide range of reactions due to effective absorption and reversible surface reactions with a wide range of species including H2, 12,14,20,36,37 CH2O, 20,23 CH4, 38 and CO. 15,20,39,40 A wide range of hydrogenation, 41 dehydrogenation, 42 oxidation, 20,40,[43][44][45] reduction, 46 and decomposition 20,[47][48][49][50][51] reactions of many organic and some inorganic 46,51 species are catalysed by PdAg. Selectivity for targeted bond scission (such as C-Cl and C-Br) on PdAg surfaces have also been demonstrated.…”
Section: Catalysismentioning
confidence: 99%
“…Selectivity for targeted bond scission (such as C-Cl and C-Br) on PdAg surfaces have also been demonstrated. 52 These catalytic reactions are heterogeneous (gas-solid or liquid-solid) in nature and many are thermally initiated, though numerous examples of PdAg alloys used for electrolysis reactions, 14,23,24,44,47,52 and electro- [53][54][55] and photocatalysis 56 have also been demonstrated. Several reactions particularly suited to use in fuel cells, such as the oxygen reduction reaction (Equation 2) are effectively performed using PdAg electrodes.…”
Section: Catalysismentioning
confidence: 99%
“…Furthermore, the as-prepared Pd nanoparticle-modified carbon ionic liquid electrode (PdNPs/CILE) was employed for the determination of H 2 O 2 via electrochemical reduction by using cyclic voltammetric (CV) and amperometric methods. CILE and nanoparticles modified by CILE have been known to be a very suitable electrode for the oxidation or reduction of a wide range of analytes [38,39]. The results showed that the PdNPs/CILE has high sensitivity and selectivity, wide linear range, and good stability for the determination of H 2 O 2 in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%